La preparación de las familias en el cumplimiento de su función educativa de los niños y niñas de 3 a 6 años con discapacidad física motriz de la parroquia Atahualpa - Panimboza Franco, Yanina del Rocío (2017)
The preparation of the families in the fulfillment of their educational function of the children of 3 to 6 years with physical motor disability of the Atahualpa Parish. The problem investigated is in the Atahualpa parish where the majority of parents of children with physical motor disabilities from 3 to 6 years of age do not fulfill their educational functions and see the need to prepare them to increase their participation in the activities schoolchildren of their sons and daughters. The research methodology seeks to analyze the theoretical references on the preparation of families of children with physical motor disabilities in their educational function, determine the current state of preparation of families in their educational functions, select training actions that contribute to the preparation of families in the fulfillment of their educational function………….